Angle-Multiplexing Nonlinear Holography for Controllable Generations of Second-Harmonic Structured Light Beams - Yao, Wenzhe; Zhou, Chao; Wang, Tianxin; Chen, Pengcheng; Xiao, Min; Zhang, Yong (Frontiers in Physics, 2021)
Nonlinear multiplexing holography emerges as a powerful tool to produce structured lights at new wavelengths. In this work, we propose and experimentally demonstrate an angle-multiplexing nonlinear holography in an angular noncritical phase-matching configuration. In experiment, various types of structured light beams, such as vortex beam, Airy beam and Airy vortex beam, are simultaneously output at second-harmonic waves along different paths. Because of the large angular acceptance bandwidth of noncritical phase-matching, one can achieve high conversion efficiency of angle-multiplexing nonlinear holography. Our method has potentially applications in high-capacity holographic storage and security encryption.